Personal health assessment, help seeking behavior and degree of family support on elderly - Asenjo, Pearl Joy Lampasa
The study was conducted to find out the way elderly assess their health, ways of seeking help in their health related problems and degree of family support. Fifty (50) elderly from Brgy. Tiolas, San Joaquin, Iloilo ages 60-80 years old and living with their families at the time of the study participated. Results showed that elderly do tend to assess their health with less strict standard.